THE IDENTIFICATION OF CONTRIBUTION OF GOVERNMENT GALLERY IN SUPPORTING INDONESIAN FINE ARTS DEVELOPMENT (CASE STUDY OF INDONESIAN NATIONAL GALLERY MANAGEMENT SYSTEM) - Cholis, Henri (Acintya, 2009)
The research examines the existence of Indonesian National Gallery in Jakarta. The Indonesian National Gallery is managed by the government. The focus of the research is in the contribution of Indonesian National Gallery in Indonesian fine arts development, especially in the local fine arts development and to understand strategy or effort of Indonesian National Gallery in managing an organization for fine arts activities and its stake holder’s network. The research also discusses a glance about management problems applied in the National Gallery. The research method, research kind or research model is a qualitative descriptive research, by using phenomenology and curatorial approach which is the management of Indonesian national Gallery and phenomena of the result of the interaction between the subjects involved in the Indonesian National Gallery activities, and understand the situation, the events, and the meaning existed in Indonesian  National Gallery. Data are collected from interviews, especially person involved in the structure of Indonesian National Gallery organization and several persons related with the existence of the gallery, such as artist and curator. Another data is book taken from Indonesian National Gallery and also the books containing articles about the gallery and the pictures used as the observing technique in this research. Data collecting uses open interview technique (not structured natural interview), direct observation with situation observer, events, and everything related with the events happened in Indonesian National gallery. Data analysis uses cycle analysis related each other which is interactive analysis related with several steps: data collection, data reduction, data presentation and conclusion. Research result: Indonesian National Gallery is able to stand and exist and experience long journey because of the strong efforts from the government officials in the department of education and culture. The facilities and the infrastructures of Indonesian national gallery is quite representative even though the building used is a former school, at first it is not designed to become a gallery. The contribution of Indonesian National Gallery is very wide; it is opened for everyone for education, training, information service, and appreciation purposes. Indonesian National Gallery opens itself for cooperation inter related instances existed in several regions. It also provides place for the person wanting to held exhibition there. National Gallery management is quite good proven by many art activities held in regional, national, and even international level which has been conducted successfully. The collection of fine arts works in Indonesian National gallery is quite many with 1750 fine arts works; some of them are a grant from foreign countries. The existence of chosen curator make Indonesian National Gallery has a good image in Indonesian fine arts. And no less important, Indonesian National gallery always keeps its quality by using selection system for everyone who proposes to make exhibition there, both from the invitation from Indonesian National Gallery and from the proposal proposed by the artist who desire to held exhibition there. Key word:  Gallery , management, contribution.